2018
DOI: 10.4103/ccd.ccd_28_18
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of remineralization potential of casein phosphopeptide- amorphous calcium fluoride phosphate and novamin on artificially demineralized human enamel: An In vitro study

Abstract: Aim:This study aimed to quantitatively compare the remineralization potential of casein phosphopeptide-amorphous calcium fluoride phosphate (CPP-ACFP) and Novamin on artificially induced enamel subsurface lesions using scanning electron microscope-energy dispersive X-ray (SEM-EDX).Materials and Methods:Enamel specimens were prepared from seventy caries-free premolars and were kept for demineralization for 4 days. Following demineralization, enamel specimens were assigned to three groups: (1) Control group, (2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 15 publications
0
26
0
Order By: Relevance
“…The use of milk and milk products, having a protective effect against the development of dental caries, has been a novel concept in remineralization. The anticariogenic properties of milk is due to the presence of casein, calcium and phosphate, which are responsible for resistance to acid dissolution (5,6). One such, remineralizing agent which has been extensively studied and accepted is casein phosphopeptide amorphous calcium phosphate (CPP-ACP).…”
Section: Introductionmentioning
confidence: 99%
“…The use of milk and milk products, having a protective effect against the development of dental caries, has been a novel concept in remineralization. The anticariogenic properties of milk is due to the presence of casein, calcium and phosphate, which are responsible for resistance to acid dissolution (5,6). One such, remineralizing agent which has been extensively studied and accepted is casein phosphopeptide amorphous calcium phosphate (CPP-ACP).…”
Section: Introductionmentioning
confidence: 99%
“…As the remineralization of enamel requires the availability of Ca and P in the oral environment, materials providing essential elements for remineralization are needed. Among these, CPP-ACP (Recaldent™) emerged as a novel material that prevented demineralization, and showed enhanced remineralization of initial enamel lesions in vitro and in vivo studies [18,[20][21][22][23][24][25]. Additionally, the concomitant use of CPP-ACP (Recaldent™) JOURNAL OF ORAL & MAXILLOFACIAL RESEARCH Zeitouny et al…”
Section: Discussionmentioning
confidence: 99%
“…In the oral environment, CPP-ACP binds to biofilms, plaque, bacteria, hydroxyapatite, and soft tissue, buffers the free Ca and phosphate ion activities and increases the degree of saturation by Ca and P with respect to hydroxyapatite. Thus CPP-ACP localizes bioavailable ions and subsequently ACP on the tooth surface [15]. Only, a very limited number of studies had evaluated factors modifying the remineralization potential of CPP-ACP quantitatively, especially the Ca and P content, and Ca/P of enamel [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…CPP-ACP adheres intraorally to plaque pellicle, hydroxyapatite as well as soft tissues, and was shown to buffer the free calcium and phosphate ion activities, maintain a state of super-saturation with respect to tooth enamel, prevent enamel demineralization, and promote remineralization [14]. A series of studies and systematic reviews [15,16] have reported an anti-caries effect of CPP-ACP. CCP-ACP with 0.2% sodium fluoride (Recaldent™ GC Corporation; Tokyo, Japan) is delivered in many forms including tooth mousse, toothpastes, mouth rinses, chewing gums, sports drinks, as well as in dental varnishes [11,17].…”
Section: Introductionmentioning
confidence: 99%